Reciprocal Relationship Between HDAC2 and P-Glycoprotein/MRP-1 and Their Role in Steroid Resistance in Childhood Nephrotic Syndrome - Singh, Harshit; Agarwal, Vikas; Chaturvedi, Saurabh; Misra, Durga Prasanna; Jaiswal, Akhilesh Kumar; Prasad, Narayan (Frontiers in Pharmacology, 2019)
Background Reduced HDACs levels have been reported in steroid resistant chronic obstructive pulmonary disease and bronchial asthma patients. P-glycoprotein (P-gp) overexpression in peripheral blood mononuclear cells (PBMCs) has been reported in patients with steroid resistant nephrotic syndrome (NS). Whether and how HDACs and P-gp are linked with each other is not clear, especially in NS patients. Aim: To evaluate the expression of mRNA of P-gp/MRP-1 and HDAC2 in PBMCs of steroid sensitive (SSNS) and steroid resistant nephrotic syndrome (SRNS) patients, and to study the relationship between expression of HDAC 2 and P-gp/ MRP-1. Methods Twenty subjects 10 each, SSNS (mean age 7.54±3.5 years), and SRNS (mean age 8.43±3.8 years) were recruited. mRNA expression of HDAC2 and P-gp/MRP-1 was studied by quantitative real time PCR. PBMCS were treated with Theophylline, 1µM, and Trichostatin A, 0.8µM, for 48 hours for induction and suppression of HDAC2. Results At baseline, expression of P-gp (4.79±0.10 v/s 2.13±0.12, p<0.0001) and MRP-1 (3.99 ±0.08 v/s 1.99 ±0.11, p<0.0001) on PBMCs was increased whereas, HDAC2 mRNA levels (2.97 ± 0.15 v/s 6.02 ± 0.13, p<0.0001) were significantly decreased in SRNS as compared to that of SSNS patients, Compared to baseline, theophylline reduced the expression of mRNA of P-gp and MRP-1 (fold change 2.65 and 2.21, *p<0.0001 in SRNS) (fold change 1.25, 1.24, *p<0.0001 in SSNS ). However it increased the expression of HDAC2 (fold change 5.67, *p<0.0001 in SRNS)(fold change 6.93, *p<0.0001 in SSNS). Compared to baseline, TSA treatment increased mRNA levels of P-gp and MRP-1 (fold change 7.51, 7.31, *p<0.0001 in SRNS) and (fold change 3.49, 3.35, *p<0.0001 in SSNS). It significantly decreased the level of HDAC2 (fold change1.50, *p<0.0001 in SRNS) (fold change2.53, *p<0.0001 in SSNS) patients. Conclusion Reduced HDAC2 activity may contribute to SRNS and HDAC2, and P-gp/MRP-1 are in reciprocal relationship with each other.